EKSISTENSI MEDIA SOSIAL INSTAGRAM: PRESERVASI BUDAYA DIGITAL DI RUMAH BUDAYA KRATONAN - Nur Wakhidah; Anggiana Indrias; Mega Alif Marintan (2025)
Technological developments have transformed cultural preservation into a digital preservation effort. Cultural preservation can now be carried out through social media, including Instagram. This effort is undertaken to save culture from fading away and to facilitate the dissemination of information about culture to the wider community, particularly through the virtual world. The purpose of this study is to analyze the use of Instagram by Rumah Budaya Kratonan in its digital cultural preservation efforts. Additionally, it aims to analyze the features used and the content presented in each post. This study employs a qualitative method with a content analysis approach. Data analysis was conducted on the Instagram social media account of Rumah Budaya Kratonan. The findings reveal that Rumah Budaya Kratonan has leveraged Instagram as a technological platform to assist in the implementation of digital cultural preservation. Rumah Budaya Kratonan utilizes various features on Instagram to preserve existing cultures. In preserving various cultures, Rumah Budaya Kratonan uses Instagram features such as feed, story, reels, and live. The types of content shared through the Rumah Budaya Kratonan Instagram account are photos and videos showcasing culture or its values.